[Kapit sa patalim ; In search of a father ; Kuro-kuro ng isang kompositor [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
Tackles on Philippine economic problem during Pres. Aquino's administration; Amerasian children in search for their father and their social conditions; and, Gary Granada's songs and his interpretations on each composition.